Spring migration of Greenland White-fronted Geese through Iceland - Francis, I S; Fox, A D (Wildfowl, 1987)
A census of staging Greenland White-fronted Geese Anser albifrons flavirostris was carried out in south and west Iceland between 19th April and 9th May 1986. A total of 3,465 birds was recorded, with 2,027 in the south and 1,438 in the west. Although some interchange of birds between areas was possible, it is considered that the recorded total represents a minimum figure (16% of the population) for Greenland White-fronts staging in Iceland in spring. Sightings of 41 birds neck-collared at Wexford, Ireland, indicated that Whitefronts wintering in Ireland stage in both south and west Iceland. Of the total number of birds found, 80% were feeding on improved hayfields and 20% on unimproved wetlands. The implications of this in the light of continuing extensive wetland drainage in Iceland are not clear but may increase the risk of disturbance and allow a larger total of White-fronted Geese to be shot than at present.